Information Provision, Incentives, and Attention: A Field Experiment on Facilitating and Influencing Managers' Decisions - Kathrin Manthei; Dirk Sliwka; Timo Vogelsang (Institute of Labor Economics (IZA), 2021)
The core role of managerial accounting is to provide information to facilitate managers' decisions and influence their behavior through incentives. We study the impact of these two roles of information on profits by implementing a field experiment in a large retail chain. In a 2 2 factorial design, we vary: (i) whether store managers obtain access to decision-facilitating accounting information on the profit margins of individual products and (ii) whether they receive performance pay based on an objective profit metric to influence their decisions. We find that both practices increase profits significantly, albeit through different behavioral channels. In particular, managers make use of the information provided by placing higher-margin products, thereby raising the gross profit margin. While we hypothesized a priori that both practices are complements, we find that the profit increases induced by the combined intervention do not significantly exceed those of the separate interventions. We attribute this finding to an attention-directing role of the interventions toward the objective of raising profits, thereby inducing a countervailing substitution effect. We show that this effect fades over time such that the combined intervention tends to induce more persistent profit increases.
Keywords: J33; M52; C93; 330; management controls; performance pay; monetary incentives; decision-facilitating; decision-influencing; accounting information; field experiment; complementarity